Sarcoptes scabiei mites in humans are distributed into three genetically distinct clades. (December 2015) - Andriantsoanirina, V.; Ariey, F.; Izri, A.; Bernigaud, C.; Fang, F.; Charrel, R.; Foulet, F.; Botterel, F.; Guillot, J.; Chosidow, O.; Durand, R.
Abstract: Scabies is an ectoparasitic infestation caused by the mite Sarcoptes scabiei. Currently, S. scabiei is taxonomically divided into different varieties on the basis of host origin. Genetics-based research on scabies has been conducted, but the data on genetic diversity of populations of this mite in humans in Europe are lacking. We evaluated the genetic diversity of populations of S. scabiei. A large series of mites obtained from humans in France and the data of mites from various hosts and geographical areas retrieved from GenBank were included to investigate whether mites are divided into distinct populations. The study of cytochrome c oxidase subunit 1 gene polymorphisms were found to be best suited for phylogenetic analysis. S. scabiei mites were distributed into three genetically distinct clades, with most mites clustering in clades B and C. The Fst value and the Nm value calculated for mites included in clades B and C indicated a strong population structure and a very low gene flow between mites of those clades. The results of the present study not only support the rejection of the hypothesis of panmixia for S. scabiei in humans but also suggest that mites belonging to different clades are genetically isolated. Moreover, the results suggest that the subdivision of S. scabies in varieties according to animal or human hosts is not warranted. In conclusion, S. scabiei mites in humans do not constitute a homogeneous population. Further investigations are now required to assess whether different clinical forms of scabies are associated with particular haplotypes or clades.